TRANSFORMATION OF DA'WAH TOWARDS CHANGING GORONTALO COMMUNITY BEHAVIOR : (Study of Ustad Muhammad Iqbal Pakaya's Da'wah Model) - Wahidah Suryani; Arfan Nusi; Indra Dewi Sery Yusuf (Farabi, 2023)
This research is a study of da'wah in Gorontalo City known as Serambi Medina. This study is a descriptive-qualitative field research. The data were obtained through free and in-depth interviews with resource persons and observations made in several Ust da'wah assemblies. Iqbal Pakaya. With a semi-biographical approach, researchers studied the da'wah carried out by a well-known preacher in Gorontalo, Ust. Muhammad Iqbal Pakaya who has a unique style of lectures. This distinctive way of da'wah turned out to have its own place in the hearts of the people of Gorontalo. Whenever Ustad Muhammad Iqbal was present, people were captivated and did not leave before the event was over. Not only the way of da'wah is alluring, Ust's da'wah material. Iqbal Pakaya was in accordance with the conditions and needs of his mad'u (object of da'wah). The concept and model of da'wah ustad Muhammad Iqbal Pakaya discusses more everyday things that are close to mad'u accompanied by the concept of humor so that it is easy to understand.